Levocarnitine for the Treatment of Polymorbid Patients - A. P. Pereverzev; D. A. Shevchenko; A. V. Filippova; A. A. Kirichenko; I. F. Krotkova; O. D. Ostroumova (Столичная издательская компания, 2020)
Effective and safe treatment of patients with polymorbidity is an urgent task of modern healthcare. Of particular difficulty is the treatment of patients with cardiovascular comorbidity, which requires an integrated approach to the treatment and development of a special, so-called patient-oriented approach. Modern scientific evidence proposes the use of levocarnitine, as part of complex therapy to increase its effectiveness. So, it was shown that levocarnitine can have a beneficial effect on blood pressure in patients with hypertension, especially those who are overweight and obese. Levocarnitine is also effective in the treatment of heart failure, which has been studied in several clinical studies, which demonstrated its ability to increase the ejection fraction of the left ventricle, stroke volume of blood and other indicators. Optimization of the bioavailability of nitrogen oxide (NO) and a decrease in systemic oxidative stress while taking levocarnitine plays an important positive role in complex therapy in patients with coronary artery disease: exertional angina and post-infarction cardiosclerosis, reducing the number of anginal attacks. Since levocarnitine has powerful antioxidant effects, it also has the neuroprotective effect found in in vitro studies in animal experiments. In case of impaired renal function, due to accelerated elimination and impaired reabsorption, a deficiency of levocarnitine in the body tissues develops, and therefore the US Food and Drug Administration (US FDA) decided on the possibility of using levocarnitine in patients on hemodialysis. Thus, taking into account the positive effects of levocarnitine in a number of frequently combined diseases, it can be considered as the drug of choice in the treatment of patients with polymorbidity.